Analysis of the Turkish Consumer Electronics Firm using SWOT-AHP method - Seker, Sukran; Ozgurler, Mesut (ELSEVIER SCIENCE BV, 2012)
SWOT analysis is a strategic planning method used to evaluate the Strengths, Weaknesses/Limitations, Opportunities, and Threats involved in a project or in a business venture. It involves specifying the objective of the business venture or project and identifying the internal and external factors that are favorable and unfavorable to achieve that objective. Turkish electronics industry is continuously working to produce innovative, high quality and globally competitive products. The Turkish electronics industry began to develop rapidly in the second half of the 80's. In this study, SWOT Analysis was used as a method to analyse a consumer electronics company from Turkey and we determined strategies according to the SWOT factors. Analytic Hierarchy Process (AHP) method is integrated to support decision situation about strategies which is determined with SWOT analysis. So the SWOT matrix is converted into a hierarchic structure and the model is analyzed with the Analytic Hierarchy Process.
Keywords: Strategic management; SWOT analysis; AHP; Consumer electronics; MANAGEMENT; TOOL; Business & Economics